PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI SEKOLAH DASAR NEGERI 004 DESA SUNGAI KUBU KECAMATAN KUBU KABUPATEN ROKAN HILIR 2019 - Afriani, Rini; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Clean and healthy lifestyle (PHBS) is one of the behaviors related to one's efforts or activities to improve their health based on awareness, so as to prevent diseases and play an active role in realizing a healthy environment by regular exercise, not smoking, adequate rest and lifestyle positive ones. The school is a second place after home to get PHBS learning and guidance. 004 Public Elementary School is one of the schools in Sungai Kubu Village, Kubu District, Riau Rokan Hilir Regency. Schools was founded in 1975 and until now students / I in this school numbered 207 people. The purpose of this study was to determine the implementation and factors that influence the implementation of PHBS in SD N 004 Sungai Kubu Village. This study uses descriptive quantitative methods. From the results of the research that has been done, the implementation of PHBS in SD N 004 Village Sungai Kubu has reached full moon health totaling 67.90% and healthy madness 32.10%. and the factors that influence PHBS in SD N 004 Sungai Kubu Village, namely regulations or placards about PHBS that are available but inadequate, PHBS socialization is rarely done, and PHBS facilities and infrastructure are available but inadequate such as toilet cleaning tools SD N 004 Sungai Kubu Village . Â Keywords: PHBS, 004 State Elementary School Sungai Kubu Village